2011
DOI: 10.1063/1.3556565
|View full text |Cite|
|
Sign up to set email alerts
|

Balanced carrier transport in organic solar cells employing embedded indium-tin-oxide nanoelectrodes

Abstract: In this paper, we present evidence of balanced electron and hole transport in polymer-fullerene based solar cells by means of embedded indium-tin-oxide nanoelectrodes. Enabled by a controllable electrochemical deposition, the individual nanoelectrodes are uniformly enclosed by a poly͑3,4-ethylenedioxythiophene͒ hole-conducting layer, allowing a relatively short route for holes to reach the anode and hence increasing the effective hole mobility. Consequently, the power conversion efficiency and photogenerated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 17 publications
0
30
1
Order By: Relevance
“…The incorporation of metal NPs into PEDOT:PSS increased both the surface roughness of the PEDOT:PSS layer and the PEDOT:PSS/P3HT:PCBM interface area. It has been reported that an increased surface roughness of the buffer layer as well as an enlarged interface area of PEDOT:PSS/P3HT:PCBM lead to shortening of the hole-extraction route and enhancement of the hole-collection efficiency by the anode [15,22,25]. The reduced series resistance ( R s ) from 1.8 to 1.5 Ωcm 2 in Table 1 is another indicator of the improved hole collection and ultimately, the enhancement of J sc and FF.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of metal NPs into PEDOT:PSS increased both the surface roughness of the PEDOT:PSS layer and the PEDOT:PSS/P3HT:PCBM interface area. It has been reported that an increased surface roughness of the buffer layer as well as an enlarged interface area of PEDOT:PSS/P3HT:PCBM lead to shortening of the hole-extraction route and enhancement of the hole-collection efficiency by the anode [15,22,25]. The reduced series resistance ( R s ) from 1.8 to 1.5 Ωcm 2 in Table 1 is another indicator of the improved hole collection and ultimately, the enhancement of J sc and FF.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the incorporation of Au NPs only in PEDOT:PSS increases the interfacial contact area between the P3HT:PCBM and PEDOT:PSS, allowing more efficient hole collection at the anode and hence improves J SC and FF. 14,15 Furthermore, from resistive devices of structure ITO/PEDOT:PSS (with or without Au NPs)/Al, it is found that the resistance of PEDOT:PSS reduces upon addition of NPs (Supporting information: Fig. S3 (Ref.…”
mentioning
confidence: 99%
“…The strategies that address the issue of absorption or carrier extraction all rely on decoupling optical and electrical thicknesses of solar cells. For example, solar cell configurations such as radial junction nanowire (NW) PV [3,4], and projected electrodes [5,6] focus on decoupling the light absorption from the carrier extraction length by absorbing light vertically, but separating the carrier laterally. These structures provide a shorter and more efficient path for carrier collection.…”
Section: Introductionmentioning
confidence: 99%